Performance of coronary calcium score and epicardial fat volume in early diagnostic of coronary artery disease. (25th November 2020) - Agoston Coldea, L; Zlibut, A; Cionca, C; Muresan, I; Horvat, D; Revnic, R; Cojan-Minzat, B.O; Gonciar, D; Mocan, T
Abstract: Background: Coronary artery disease (CAD) remains a world leading cause of death, despite the development of traditional risk scores based on the quantification of cardiovascular risk factors. Coronary calcium score (CCS) determined by cardiac computed tomography (CCT) is a noninvasive tool with major implications in early diagnosis and in outcome prediction in CAD patients. Epicardial fat volume (EFV) is a recently described CCT-based diagnostic and prognostic tool of CAD and outcome. Purpose: This study sought to investigate the performance of coronary calcium score and EFV in early diagnosing CAD. Methods: We conducted a prospective, single-center, cross-sectional study on patients suspected of CAD. All patients were submitted to detailed clinical data, 12-lead electrocardiogram, estimating pretest probability, stress test, echocardiography, CCT imaging. In the study subjects was assessed CCS, EFV and the number of calcified plaques (NoP). The total CCS load was then ranked in the following scoring groups: 0 (no evidence of coronary calcium; reference group), 1–99 (minimal to mild), 100–399 (moderate), and 400–999 (extensive) and ≥1000 (very extensive). The subjects in the study were classified according to the NoP derived from their CCS scans (no plaques, 1–5, 6–10 and more than 10 calcified plaques). CAD was defined as coronary stenosis over 50% of the vessel. Results: Among 540 patients (55.8±11.2 years of age; 52% women) met the enrollment criteria, 98 patients presented CAD. Spearman correlation analysis revealed strong correlations between EFV index and CCS (r=0.45; p<0.0001) and between EFV index and NoP (r=0.44; p<0.0001), after adjustment for age, sex, body mass index, hypertension, diabetes and low-density lipoprotein cholesterol. The area under the curve of the receiver-operator curve for CAD prediction by CCS >70.3 UH (cut-off value) was significantly higher (AUC=0.927; p<0.0001) by comparison with EFV index >40.8 ml/m 2 (AUC=0.816; p<0.0001) and NoP >4 (AUC=0.928; p<0.0001). The association of all three parameter, CCS, EFV and NoP, increases the prediction power of CAD, providing an AUC of 0.969 with a 0.70 sensibility and 0.95 specificity. Conclusion: The combined use of EPV, CCS and NoP has a very high predictive capacity for CAD, regardless of the classic cardiovascular risk factors. This increases the diagnostic capacity of CAD beyond every parameter used alone. Funding Acknowledgement: Type of funding source: None